PRACTICAL APPLICATION OF AUDIOVISUAL MATERIALS IN ENGLISH TEACHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the practical significance and effectiveness of employing audiovisual materials (AVM) in contemporary English language classrooms. The study analyzes the impact of video content, interactive platforms, and authentic audio recordings on the development of students' listening comprehension and speaking proficiency. A comparative analysis between traditional teaching methodologies and audiovisual-integrated approaches is presented. The findings suggest that these technological tools not only enhance pedagogical efficiency but also significantly foster student engage